The device for measurement of an ophthalmotonus at different kinds of animals - Санін, М. О. (Scientific Progress & Innovations, 2012)
The digital device for measurement of intraocular pressure (IOP) at house and agricultural animals, and also results of measurements on a reference to water column, on healthy rabbits and horses is described. There was a developed technics of measurement, and the software of the device for accuracy increase is improved.